Penemuan Hukum Sebagai Implementasi Teori Hukum Dalam Menjawab Kekosongan Norma - Indah, Reviana Mutiara; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
This research is motivated by the gap between static positive law and the continuously evolving dynamics of society, which often creates a legal vacuum (rechts vacuum). This condition requires judges to abandon the old paradigm of being merely the "mouthpiece of the law" (la bouche de la loi) and to take an active role as law-creators. The objective of this research is to thoroughly analyze the concept, theoretical position, urgency, mechanism, and methods of legal discovery (rechtsvinding) conducted by judges as a solution to overcome normative gaps and to realize substantive justice. Using a normative juridical research method through statutory and conceptual approaches, and analyzed qualitatively, this study examines primary and secondary legal sources. The research findings indicate that legal discovery is a central function and a judicial obligation for judges to respond to legal vacuums, vague norms (vage normen), and conflicting norms (antinomy). Judges, as the sole authority, apply legal discovery through a systematic mechanism (konstatir, kualifisir, konstituir) using methods of interpretation and construction, although their authority is limited by the principle of legality, jurisprudence, and the judicial hierarchy. It is concluded that the practice of legal discovery in Indonesia shows a shifting trend towards a progressive approach, which is essential for keeping the law alive, adaptive, and capable of balancing the values of certainty, utility, and justice in every decision.